The Future is Feminine : capitalism and the masculine disorder - Cremin, Ciara (New York : Bloomsbury Academic, 2021)
"Carnage in the classroom, misogynists in high office, sociopaths in uniform, masculinity makes headlines and for all the wrong reasons. But the most toxic of men are an index of a broader problem with the way males are raised and learn to interact. Designated male at birth, Cremin knows what it means to be masculinised. Now she offers a trans woman's perspective on and diagnosis of what provocatively she describes a disorder. It's a disorder of the human personality reflective of the society into which we are born. Primed to be competitive and violent, and compelled to kill off parts of the self because of their feminine associations, the masculinised male, Cremin says, is suited to capitalism's monstrous and unquenchable needs. She draws on marxist and psychoanalytic theory both to diagnose the condition and also, importantly, to theorise how individually and collectively it might be overcome. Rejecting the idea that males are inherently violent and females inherently nurturing or that there's such a thing as a masculine or feminine essence, Cremin proclaims nevertheless that, as she conceives the terms, femininity is the riddle of a masculine disorder solved, and it knows itself to be this solution. The future is feminine. It must be"--
Includes bibliographical references and index.
Keywords: Femininity; Women -- Psychology; Masculinity; Men -- Psychology; Capitalism -- Social aspects; Masculinity; Men--Psychology; Women--Psychology; Capitalism--Social aspects; Femininity